Biological age acceleration and mortality risk among U.S. adults with cardio-kidney-metabolic syndrome, stages 0–3 - Xiaoqiang Chen; Yisen Huang; Yingxuan Huang; Yingyi Li; Xinqi Chen; Yubin Wang; Xiaoqiang Liu (Medicine, 2026)
This study aims to evaluate the associations of Klemera-Doubal Method Biological Age Acceleration (KDM-BAA) and Phenotypic Age Acceleration (PAA) with all-cause and cause-specific mortality in U.S. adults with Cardio-Kidney-Metabolic (CKM) syndrome stages 0–3 and to establish risk prediction models. Data were obtained from 16,837 participants in NHANES 1999–2010 and 2015–2018, linked to mortality through 2019. Biological age was estimated using KDM-BA and Phenotypic Age algorithms, with residuals defining Biological Age Acceleration (BAA). Cox proportional hazards models were applied, and LASSO-Cox nomograms were developed for mortality prediction. Over a median follow-up of 11.33 years, 10.8% of the weighted population (9.75 million adults) died. After full adjustment for confounders, KDM-BAA positivity increased the risk of all-cause, CVD, and non-CVD mortality by 41%, 74%, and 31%, respectively; PAA positivity showed even larger increases – 103%, 79%, and 112%. Both metrics consistently exhibited a positive association in multiple subgroups and sensitivity analyses. The LASSO-Cox-based nomogram showed favorable discrimination (training AUCs 0.776 and 0.775 at 10 and 20 years; validation AUCs 0.765 and 0.757, respectively) and good calibration, suggesting potential clinical applicability. BAA independently predicts long-term mortality among individuals with CKM stages 0–3. PAA provides superior prognostic value, supporting the importance of monitoring biological aging to guide early intervention and improve long-term outcomes.